Acute Cold / Restraint Stress in Castrated Rats - Farideh Zafari Zangeneh; Ashraf Amirzargar; Akram Ahangarpour (Tehran University of Medical Sciences, 2008)
Objective: The present study aimed to determine whether castration altered osmotically stimulated vasopressin (VP) release and urinary volume and what is the role of endocrine-stress axis in this process. Materials and methods: Totally 108 mice were studied in two main groups of castrated (n=78) and control (n=30). Each group was extracted by acute cold stress (4◦C for 2h/day), restraint stress (by syringes 60cc 2h/day) and cold/restraint stress. The castrated group was treated in sub groups of testosterone, control (sesame oil as vehicle of testosterone). Propranolol as blocker of sympathetic nervous system was given to both groups of castrated mice and main control. Results: Our results showed that, there is interactions between testosterone and sympathetic nervous system on vasopressin, because urine volume was decreased only in testoctomized mice with cold/restraint and cold stress (P<0.001); propranolol as the antagonist of sympathetic nervous system could block and increase urine volume in castrated mice. This increased volume of urine was due to acute cold stress, not restraint stress (p<0.001). The role of testosterone, noradrenalin (NA) and Vasopressin (VP) in the acute cold stress is confirmed, because testosterone could return the effect of decreased urine volume in control group (P<0.001). Conclusion: Considering the effect of cold/restraint stress on urinary volume in castrated mice shows that there is interaction between sex hormone (testosterone), vasopressin and adrenergic systems.